Karaterisitik Buangan Akhir Pengolahan POME PT. XYZ - Basopi, Hasbi; Andrio, David; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Problem of Palm oil mill industry is POME final discharge failed to comply discharge standard and brownish black color in POME final discharge inhibits the growth of aquatic biota and must be treated to avoid environment pollution which affect the environment health. Before the treatment, the characteristics of POME final discharge should be determined in order to attain the proper action. This study aims to describe the characteristics and quality of the COD, SS and color POME final discharge. Based on the result of laboratory test on samples of POME final discharge showed values for the each parameter are COD 2202 mg/l, SS 320 mg/l and color 8080 Pt.Co. The result of POME final discharge is not eligible according to standard of Environmental Ministry Decree No.5 of 2014 concerning Oil Industry Wastewater Quality Standard. Therefore, POME final discharge treatment is required to protect the environment from further pollution. Keywords : POME final discharge, COD, SS, color